A New Sythetic Hybrid (A1D5) between Gossypium herbaceum and G. raimondii and Its Morphological, Cytogenetic, Molecular Characterization. - Yuxiang Wu; Di Chen; Shuijin Zhu; Lufei Zhang; Lingjiao Li (PLoS ONE)
The diploid species G. herbaceum (A1) and G. raimondii (D5) are the progenitors of allotetraploid cotton, respectively. However, hybrids between G. herbaceum and G. raimondii haven't been reported. In the present study, hybridization between G. herbaceum and G. raimondii was explored. Morphological, cytogenetic and molecular analyses were used to assess the hybridity. The interspecific hybrid plants were successfully obtained. Most of the morphological characteristics of the hybrids were intermediate between G. herbaceum and G. raimondii. However, the color of glands, anther cases, pollen and corolla, and the state of bracteoles in hybrids were associated with the G. herbaceum. The color of staminal columns and filaments in hybrids were associated with G. raimondii. Cytogenetic analysis confirmed abnormal meiotic behavior existed in hybrids. The hybrids couldn't produce boll-set. Simple sequence repeat results found that besides the fragments inherited from the two parents, some novel bands were amplified in hybrids, indicating that potential mutations and chromosomal recombination occurred between parental genomes during hybridization. These results may provide some novel insights in speciation, genome interaction, and evolution of the tetraploid cotton species.